Modal Sosial Dalam Penguatan Kelembagaan Kelompok Tani: Tinjauan Literatur Sistematis dan Pemetaan Bibliometrik - Vivi Hendrita; Edi Firnando (LPPM Universitas Malikussaleh - Indonesia, 2026)
Social capital plays an important role in strengthening farmer groups, promoting collective action, and enhancing the resilience of smallholder farmers. However, research on social capital in the agricultural sector remains fragmented and lacks integration across theory, context, characteristics, and methodology. This study aims to systematically examine and map the development, intellectual structure, thematic trends, and research gaps regarding social capital in farmer groups through a systematic literature review approach and bibliometric analysis based on the TCCM framework. A set of Scopus-indexed peer-reviewed articles was analyzed using VOSviewer to identify publication trends, keyword linkages, and major thematic clusters. The results indicate that social capital occupies a central position in farmer group research and is closely associated with smallholder farmers, collective action, cooperatives, climate change adaptation, and agricultural development. Despite its growing attention, most studies continue to emphasize social networks and economic outcomes, while the internal dimensions of social capital—such as trust, norms, and participation—and their role in strengthening farmer group institutions remain underexplored. This study highlights the need for stronger integration between theoretical perspectives, local contexts, social capital characteristics, and diverse methodological approaches. The findings provide a foundation for future research agendas and offer insights for designing more effective and sustainable farmer group empowerment strategies based on social capital.